TESTING EDLINK'S ABILITY TO MANAGE BLENDED LEARNING - Akbar Nasrum; Sufri Mashuri; Made Subawo (USN Kolaka, 2024)
The main purpose of this research is to find out the advantages and disadvantages of the sevima edlink application through application in lectures using mixed methods. The advantages and disadvantages obtained are expected to be input for the university for the development of a better campus LMS. A good LMS will support the implementation of good MBKM through distance learning programs. In addition to finding out the advantages and disadvantages of Edlink, another important point is to involve students including lecturers involved to actively participate in using learning technology. This is one of the important points of this research. The methods used were case study, in-depth interview and participative observation. The research instruments were questionnaires and interview guidelines. The results of this study indicate that edlink is very feasible to use as a campus LMS although there are some features that must be improved.